Spanish translation and validation of the EMPATHIC-30 questionnaire to measure parental satisfaction in intensive care units - Francisco Javier Pilar Orive; Jasone Basabe Lozano; Aurora López Zuñiga; Yolanda M. López Fernández; Julene Escudero Argaluza; Jos M. Latour (Elsevier, 2018)
Introduction: Few validated surveys measuring parental satisfaction in the Paediatric Intensive Care Unit (PICU) are available, and none of them in Spanish language. The aim of this study is to translate and validate the questionnaire EMpowerment of PArents in THe Intensive Care (EMPATHIC). This questionnaire measures parental perceptions of paediatric intensive care-related satisfaction items in the Spanish language. Material and methods: A prospective cohort study was carried out using questionnaires completed by relatives of children (range 0-17 years old) admitted into a tertiary PICU. Inclusion criteria were a length of stay more than 24 h, and a suitable understanding of Spanish language by parents or guardians. Exclusion criteria were re-admissions and deceased patients. The questionnaire was translated from English to Spanish language using a standardised procedure, after which it was used in a cross-sectional observational study in order to confirm its validity and consistency. Reliability was estimated using Cronbach's α, and content validity using Spearman's correlation analysis. Results: A total of 150 questionnaires were collected. A Cronbach's α was obtained for domains greater than 0.7, showing a high internal consistency from the questionnaire. Validity was measured by correlating 5 domains with 4 general satisfaction items, documenting an adequate correlation (Rs: 0.41-0.66, p < .05). Conclusions: The Spanish version of EMPHATIC 30 is a feasible, easy, and suitable tool in this specific environment, based on the results. EMPATHIC 30 is able to measure parental satisfaction, and may serve as a valid indicator to measure quality of care in Spanish PICUs. Resumen: Introducción: Existen pocas encuestas validadas para medir la satisfacción de los padres en las Unidades de Cuidados Intensivos Pediátricos (UCIP) y ninguna de ellas en idioma español. El objetivo de este estudio es traducir el cuestionario EMpowerment of PArents in THe Intensive Care (EMPATHIC), que mide la satisfacción y experiencias de los padres, a la lengua española y validarlo. Material y métodos: Estudio prospectivo, realizado en la UCIP de un hospital terciario mediante encuestas a los familiares de pacientes ingresados (de entre 0 y 17 años). Los criterios de inclusión fueron una estancia mayor de 24 h y una buena comprensión del idioma de los padres/tutores. Los criterios de exclusión fueron los reingresos y los pacientes fallecidos. Se realizó la traducción del cuestionario mediante un procedimiento estandarizado. Tras la traducción, se hizo un estudio observacional transversal para confirmar su validez y consistencia. La fiabilidad se estimó mediante el α de Cronbach y la validez de contenido mediante el análisis de correlación de Spearman. Resultados: Se reunieron 150 encuestas. El α de Cronbach por dominios se situó por encima de 0,7, lo que indica una alta consistencia interna del cuestionario. La validez fue medida correlacionando los 5 dominios con los 4 ítems de satisfacción general, lo que demostró una correlación adecuada (rs: 0,41-0,66; p < 0,05). Conclusiones: Basados en estos resultados, la adaptación del EMPHATIC-30 a la cultura e idioma español es un instrumento válido, de fácil cumplimentación y adecuado para el entorno estudiado, capaz de medir la satisfacción de los padres y de servir como guía para mejorar la calidad de la atención en las UCIP españolas.